2020
DOI: 10.1097/md.0000000000019755
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of high expression of proliferating cell nuclear antigen in non-small cell lung cancer

Abstract: Although proliferating cell nuclear antigen (PCNA) plays an important role in tumor proliferation and its expression level is closely related to the biological activity of tumor cells, PCNA expression in non-small cell lung cancer (NSCLC) has been seldom reported. In this study, we aimed to investigate the significance of PCNA expression in NSCLC tissues. PCNA expression in NSCLC and adjacent tissues were assessed by immunohistochemistry (IHC), western blotting, and reverse transcription polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…In addition, WB assay shown that knockdown of SENCR significantly reduced the expression of proliferation‐related protein PCNA, 20 cisplatin resistance‐related proteins MDMX 21 and P‐gp 22 in NSCLC cells (Figure 2I ), while overexpression of SENCR was reversed (Figure 2J ). These results suggested that SENCR promote proliferation and cisplatin resistance in NSCLC cells.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, WB assay shown that knockdown of SENCR significantly reduced the expression of proliferation‐related protein PCNA, 20 cisplatin resistance‐related proteins MDMX 21 and P‐gp 22 in NSCLC cells (Figure 2I ), while overexpression of SENCR was reversed (Figure 2J ). These results suggested that SENCR promote proliferation and cisplatin resistance in NSCLC cells.…”
Section: Resultsmentioning
confidence: 98%
“…PCNA has been reported to be highly expressed in many cancers, such as non-small-cell lung cancer, breast cancer, etc. ( Ye et al., 2020 ). It is suggested that miR-1307 changes the expression of cyclin-related proteins pRB, PCNA, p21waf1/cip1, GADD45, P18, and ppRB dependent on CALR-OSTC-endoplasmic reticulum protein folding pathway.…”
Section: Discussionmentioning
confidence: 99%
“…While the fourth TAAs (PCNA), it is the rst time to study the relationship between its AAbs and mammary tumors concerning that PCNA TAAs were detected in sera of diseased animals with various types of cancers such as duodenal, breast and in non-small lung cancers and considered as an important prognostic indicator of cancer. Authors added that PCNA TAA high levels of expression were closely related to the occurrence, development, and prognosis of BC [43]. Although the detection of the autoantibodies accepted a raise of interest as a tool for diagnosis, early diagnosis, and monitoring of treatment response of different therapeutic modalities in cancers including breast cancer, PCNA autoantibodies have been seldom reported.…”
Section: Discussionmentioning
confidence: 99%